FORCED COLLECTIVATION OF PEASANTS OF UZBEKISTAN AND ITS NEGATIVE CONSEQUENCES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article reveals the dark days of our history — the general collectivization in agriculture and its consequences namely in the years 1930-1933, collectivization was carried out using brutal violence and inclusion of rural population into collective farms with the completion of the kulaks. Opponents of the collectivization were mercilessly sent into exile.